2016
DOI: 10.1136/bcr-2016-217958
|View full text |Cite
|
Sign up to set email alerts
|

Minimal change disease associated with malignant pleural mesothelioma: case report and review of the literature

Abstract: A 77-year-old man with a history of asbestos exposure was admitted to our internal medicine division for generalised weakness, fatigue, loss of weight, night sweats and difficulty for breathing since 3 months. Clinical examination revealed left fine crackles and bilateral leg oedema. Blood test showed elevated C reactive protein level at 142 mg/L, lactate dehydrogenase level at 421 UI, creatinine level at 5.75 mg/dL. Serum albumin level at 30 g/L, urinalysis showed significant proteinuria at 6.4 g/L. Chest X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…The remission rate is 80-90%, and immunosuppressive agents such as cyclophosphamide, cyclosporine, or tacrolimus are rarely necessary ( 12 ). However, when MCD is secondary to a paraneoplastic syndrome, the treatment of neoplasia should be considered ( 20 ). Kofman et al reported that 18 of 13,992 cases of non-Hodgkin lymphoma showed MCD, and that relapse of MCD occurred more frequently in patients treated only by steroids (77.8%) than those receiving combined therapy with steroids and other chemotherapeutic agents (25%) ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remission rate is 80-90%, and immunosuppressive agents such as cyclophosphamide, cyclosporine, or tacrolimus are rarely necessary ( 12 ). However, when MCD is secondary to a paraneoplastic syndrome, the treatment of neoplasia should be considered ( 20 ). Kofman et al reported that 18 of 13,992 cases of non-Hodgkin lymphoma showed MCD, and that relapse of MCD occurred more frequently in patients treated only by steroids (77.8%) than those receiving combined therapy with steroids and other chemotherapeutic agents (25%) ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Debido a esto, existe un grupo de glomerulopatías paraneoplásicas descritas como clásicas, dada su relación altamente documentada con cierto tipo de neoplasias como la nefropatía membranosa asociada con tumores de pulmón, recto y próstata principalmente, y la enfermedad de cambios mínimos asociada al linfoma Hodgkin y algunos tipos de leucemias, habiendo escasos reportes sobre tumores sólidos, como el de recto, principal motivación para reportar este extraño caso [7,12,13].…”
Section: Discussionunclassified
“…Con este manejo se documentan tasas de remisión de hasta el 90 % al completar las 16 semanas [1,[15][16][17]. Sin embargo, en los casos secundarios relacionados con malignidad, el tratamiento debe ser el de la neoplasia perse, no encontrándose bene cio en el manejo con esteroides, e incluso, en algunos estudios, se documentó en este grupo de pacientes mayor riesgo de eventos adversos psiquiátricos y de recaída en los casos tratados únicamente con esteroides [4,10,12]. Esta fue la conducta establecida en nuestro paciente, quien recibió tratamiento con Capecitabina, primera línea de quimioterapia, además del manejo quirúrgico con resección del tumor a nivel local.…”
Section: Alteraciones Renales Secundarias Al Tratamiento De La Malignidad Como Lesión Renal Agudaunclassified
“…The total incidence of cancer among patients with MGN is 7.9% 2, reaching up to 22% in elderly patients 2. Since in most cases the nephrotic syndrome precedes about 6 months or appears parallel to the diagnosis of malignant pleural mesothelioma (MPM),3 it is important to perform an active search for occult neoplasia in adult patients with new-onset nephrotic syndrome, after ruling out a primary origin. The diagnosis of paraneoplastic nephrotic syndrome can be considered if the following criteria are present: (1) no evidence of other aetiology, (2) nephrotic syndrome appears 6 months before or after diagnosis of cancer, (3) cancer treatment is associated with a decrease of proteinuria and (4) tumour relapse is associated with an increase in proteinuria 1 3.…”
Section: Discussionmentioning
confidence: 99%
“…The association of MGN with pleural mesothelioma is very rare. In the review published by Yildiz H et al ,3 only 11 cases have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%